1986
DOI: 10.1037/0097-7403.12.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Control of fluid palatability by exteroceptive Pavlovian signals.

Abstract: Tastes elicit a set of palatability-dependent orofacial and somatic responses in rats. We investigated whether discrete auditory conditioned stimuli that signal the availability or onset of unconditioned taste stimuli (sucrose, quinine) can control orofacial responses in the absence of those unconditioned stimuli. In Experiment 1, one auditory stimulus (CS+) was paired with the delivery of a sucrose solution to the magazine floor, and another auditory stimulus (CS-) was never followed by sucrose. Following con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…Delamater et al (1986) observed positive TR responses to water in the presence of CSs that had been paired with sucrose either 20 (Exp. 2) or 84 (Exp.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Delamater et al (1986) observed positive TR responses to water in the presence of CSs that had been paired with sucrose either 20 (Exp. 2) or 84 (Exp.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, their assessment of TR responses might have been more sensitive than ours. Third, as Berridge and Schulkin (1989) noted, in the absence of devaluation or other such procedures, an S-R basis for the TR responses Delamater et al (1986) observed with more extended training can not be ruled out.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Oral infusions of water occurred for most rats in a context where infusions of sucrose or sucrose/quinine already had been experienced (since the order of taste presentation was random). The palatability of water can be influenced by associative experience with exteroceptive cues that have been paired with sweet or bitter tastes (Delamater, et al, 1986).…”
Section: Gustatory Targets Of Enhancement By Hungermentioning
confidence: 99%